2006
DOI: 10.1007/s00268-005-0239-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Vitamin D Status and Biochemical/Clinical and Pathological Parameters in Primary Hyperparathyroidism

Abstract: Vitamin D deficiency leads to more severe bone disease, increased parathyroid tumor growth, and delayed postoperative recovery of parathyroid function in patients with primary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 22 publications
8
51
3
5
Order By: Relevance
“…In that study, gland weight and serum levels of PTH, ALP and calcium were significantly higher in patients with serum 25(OH)D less than 15 ng/ml. Ozbey et al supported this finding [28]. In contrast, serum 25(OH)D was not significantly related to parathyroid gland size in other reports [20,17,19].…”
Section: Discussionsupporting
confidence: 34%
See 2 more Smart Citations
“…In that study, gland weight and serum levels of PTH, ALP and calcium were significantly higher in patients with serum 25(OH)D less than 15 ng/ml. Ozbey et al supported this finding [28]. In contrast, serum 25(OH)D was not significantly related to parathyroid gland size in other reports [20,17,19].…”
Section: Discussionsupporting
confidence: 34%
“…Bussey and Bruder also reported that 40 and 37% had vitamin D deficiency and insufficiency in pHPT patients, respectively [27]. Several studies suggested that vitamin D insufficiency is related with the severity of pHPT [16,28]. Serum levels of 25(OH)D were inversely related to parathyroid gland weight in the study of 148 pHPT patients [16].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The pathophysiological mechanisms responsible for the low serum 25(OH)D level in PHPT are not completely clarified. The data obtained from several studies suggest that vitamin D status might influence the clinical and biological expression of PHTP [1,2,[4][5][6][7][8][9][10][11][12][13][14][15] and even recovery after surgical treatment [11,16,17], although some authors have not found such an association [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been proposed that changes in dietary habits and the increasing use of vitamin D preparations could contribute to an increased proportion of clinically asymptomatic cases [6]. It has been estimated that 80% of PHPT cases are asymptomatic [7], familial forms representing about 5% [8].…”
Section: Introductionmentioning
confidence: 99%